2014
DOI: 10.1371/journal.pone.0100373
|View full text |Cite
|
Sign up to set email alerts
|

High Resolution Imaging Study of Interactions between the 37 kDa/67 kDa Laminin Receptor and APP, Beta-Secretase and Gamma-Secretase in Alzheimer's Disease

Abstract: Alzheimer's disease (AD) is the most prevalent form of dementia affecting the elderly. Neurodegeneration is caused by the amyloid beta (Aβ) peptide which is generated from the sequential proteolytic cleavage of the Amyloid Precursor Protein (APP) by the β– and γ- secretases. Previous reports revealed that the 37 kDa/67 kDa laminin receptor (LRP/LR) is involved in APP processing, however, the exact mechanism by which this occurs remains largely unclear. This study sought to assess whether LRP/LR interacted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 47 publications
(56 reference statements)
0
22
0
Order By: Relevance
“…The accumulation of extracellular amyloid‐β (Aβ) plaques and the formation of intracellular neurofibrillary tangles composed of hyperphosphorylated tau protein are the two hallmark features of AD (Jovanovic et al, 2014). Oligomeric Aβ is thought to be the candidate etiological agent of AD because it has been identified to induce neurotoxicity via interactions with many other proteins (Verdier and Penke, 2004; Kudo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of extracellular amyloid‐β (Aβ) plaques and the formation of intracellular neurofibrillary tangles composed of hyperphosphorylated tau protein are the two hallmark features of AD (Jovanovic et al, 2014). Oligomeric Aβ is thought to be the candidate etiological agent of AD because it has been identified to induce neurotoxicity via interactions with many other proteins (Verdier and Penke, 2004; Kudo et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…As sAPPb levels were significantly reduced upon anti-LRP/LR antibody blockade and shRNA knockdown, an interaction between LRP/LR and b-secretase (the enzyme responsible for sAPPb cleavage from APP) seemed probable. Co-immunoprecipitation between these two proteins, as well as a strong degree of co-localisation further suggested the likelihood of this; however, high-resolution imaging (super resolution structured illumination [SR-SIM]) and FRET analysis revealed that a direct interaction between these two proteins did not exist [100]. Since BACE1 and LRP/LR share several interaction partners, namely PrP c [101] and heparan sulphate proteoglycans [102], the results obtained during co-immunoprecipitation suggest a possible indirect interaction between b-secretase and LRP/LR mediated by a cellular component that interacts with both proteins.…”
Section: The Role Of Lrp/lr In Admentioning
confidence: 99%
“…The co-localisation was seen predominantly in the cytoplasmic regions of the cells, where APP processing is known to occur within the endosomes, and on the cell surface from which Ab is shed. Upon FRET analysis, a strong signal was obtained suggesting that FRET had occurred between PS1 and LRP/ LR [100], indicating that the two proteins are within 10 nm of each other --a proximity that is close enough to warrant a direct interaction.…”
Section: The Role Of Lrp/lr In Admentioning
confidence: 99%
“…The receptor is seen to be overexpressed on the surface of tumorigenic cells such as cervical, lung, prostate and colon [9, 10], breast and oesophageal [11] and liver cancer cells [12], thus serving many physiological functions such as signal transduction, cell cycle progression, cell migration, cell-matrix adhesion, cell viability and proliferation [1315]. LRP/LR is also associated with the process of Aβ- generation in Alzheimer’s disease [16, 17] as well as enhancing telomerase activity which is seen to play a role in disease progression and chemotherapy resistance in some cancers [18]. LRP/LR overexpression directly promotes the adhesion and invasion of tumorigenic cell lines via the process of metastasis.…”
Section: Introductionmentioning
confidence: 99%